Standard precautions: occupational exposure and behavior of health care workers in Ethiopia. - Ayalu A Reda (Public Library of Science (PLoS), 2010)
Background Occupational exposure to blood and body fluids is a serious concern for health care workers, and presents a major risk for the transmission of infections such as HIV and hepatitis viruses. The objective of this study was to investigate occupational exposures and behavior of health care workers (HCWs) in eastern Ethiopia. Methods We surveyed 475 HCWs working in 10 hospitals and 20 health centers in eastern Ethiopia using a structured questionnaire with a response rate of 84.4%. Descriptive statistics and multivariate analysis using logistic regression were performed. Results Life time risks of needle stick (30.5%; 95% CI 26.4-34.6%) and sharps injuries (25.7%; 95% CI 21.8-29.6%) were high. The one year prevalence of needle stick and sharps injury were 17.5% (95% CI 14.1-20.9%) and 13.5% (95% CI 10.4-16.6%) respectively. There was a high prevalence of life time (28.8%; 95% CI = 24.7-32.9%) and one year (20.2%; 95% CI = 16.6-23.8%) exposures to blood and body fluids. Two hundred thirteen (44.8%) HCWs reported that they were dissatisfied by the supply of infection prevention materials. HCWs had sub-optimal practices and unfavorable attitudes related to standard precautions such as needle recapping (46.9%) and discriminatory attitudes (30.5%) toward HIV/AIDS patients. Conclusion There was a high level of exposure to blood and body fluids among HCWs. We detected suboptimal practices and behavior that put both patients and HCWs at significant risk of acquiring occupational infections. Health authorities in the study area need to improve the training of HCWs and provision of infection prevention equipment. In addition, regular reporting and assessment of occupational exposures need to be implemented.